Efektivitas Kinerja Tata Usaha Dalam Pengembangan Sistem Informasi Manajemen Pendidikan Di Mts Negeri 1 Kepulauan Sula - Sangaji, Fitrianti (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2022)
The background of the problem in this study is to find out how much Effectiveness of Administrative Performance is in the Development of Education Management Information Systems at MTs Negeri 1 Sula Islands. This type of research uses a qualitative method with a descriptive approach, data sources are the Head of Madrasah, Head of Administration, and Administrative Staff/Staff. Data collection techniques are observation, interviews and documentation, while data analysis techniques are data reduction, data triangulation and data conclusion drawing. The results show that: (1) Administrative performance is still not effective in completing tasks or work on time as specified. Meanwhile (2) the development of the education management information system has not been maximized, the administrative understanding of the education management information system is still very limited, this is due to the different educational backgrounds of administrative employees. Conclusions (1) Implementation of high quality administrative performance . With high integrity between psychic and physical functions, the individual has good self-concentration. (2) The administrative understanding of the education management information system is still very limited due to the educational background of administrative employees who have educational degrees that are not in accordance with their fields.